What is the solution to the equation -(5-(a+1) ) = 9-(5-(2a-3) ) ?

label Algebra
account_circle Unassigned
schedule 1 Day
account_balance_wallet $5

a = -5 

a = -3

a = 3

a = 5

Aug 31st, 2015

Thank you for the opportunity to help you with your question!

a = -5

-(5-(a+1)) = 9-(5-(2a-3))    Always do the inner-most parentheses first.  When distributing a minus sign to the parenthesis, the signs will be switched.  Example: 5-(2a-3) becomes 5-2a+3

-(5-a-1) = 9-(5-2a+3)   Now simplify what's in the parentheses on both sides of the equations.

-(4-a) = 9-(8-2a)   Distribute negative sign to what's inside the parenthesis.

-4+a = 1+2a  Subtract 'a' to the right side and subtract '1' to the left side.

-5 = a




Please let me know if you need any clarification. I'm always happy to answer your questions.
Aug 31st, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Aug 31st, 2015
...
Aug 31st, 2015
Oct 17th, 2017
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer